1994
DOI: 10.1042/cs0870165
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Value of Soluble Immunological Mediators in Neonatal Infection

Abstract: 1. Infection in the neonatal period is difficult to diagnose and is a significant cause of morbidity and mortality in preterm infants. 2. We investigated prospectively the predictive value of plasma measurement of bacterial endotoxin (lipopolysaccharide), tumour necrosis factor-alpha, interleukin-6, interleukin-8, intercellular adhesion molecule-1 and C-reactive protein in 60 consecutive newborn infants suspected of having neonatal infection. Plasma samples were taken at the time of acute clinical deterioratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
36
5

Year Published

1996
1996
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 0 publications
4
36
5
Order By: Relevance
“…Previous studies on the diagnostic value of plasma IL-8 in the prediction of EOBI reported this cytokine to be more sensitive but less specific than CRP at the onset of suspected infection (7,23,27). Combining serum IL-8 with CRP improved the sensitivity from 83 to 93% without losing much specificity (7).…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies on the diagnostic value of plasma IL-8 in the prediction of EOBI reported this cytokine to be more sensitive but less specific than CRP at the onset of suspected infection (7,23,27). Combining serum IL-8 with CRP improved the sensitivity from 83 to 93% without losing much specificity (7).…”
Section: Discussionmentioning
confidence: 98%
“…Bacterial infection is still a major cause of perinatal morbidity and mortality, and the recognition of infection is difficult since the clinical and biochemical manifestations are subtle in the neonatal period [11]. New tools for diagnosing potentially life-threatening infections in these vulnerable patients are therefore needed [11].…”
Section: Introductionmentioning
confidence: 99%
“…New tools for diagnosing potentially life-threatening infections in these vulnerable patients are therefore needed [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Biomarkers are identified through a four-step process of discovery by appropriate multiplex biochemical analysis followed by replication ideally in independent cohorts, validation of diagnostic sensitivity and specificity, and translation into a clinical diagnostic test (9). Numerous candidate biomarkers have been identified in neonatal sepsis: elevated plasma or serum levels of inter-leukin 6 (IL-6) 1 (11,13), tumor necrosis factor ␣ (TNF␣) (11,13), neutrophil elastase (NE) (14), C-reactive protein (CRP) (12,15), soluble CD14 (16,17), granulocyte colony-stimulating factor (G-CSF) (18), soluble intercellular adhesion molecule-1 (ICAM-1) (12), and soluble L-selectin (19) have shown association with infection in neonates. The value of physiological measurements in this context has also been examined recently (20).…”
mentioning
confidence: 99%